Species Accumulation Curves with vegan, BiodiversityR and ggplot2 - Kindt, R. (2020)
The main objective of this document is to give some examples of how data on species accumulation curves, obtained via vegan and BiodiversityR, can be plotted via ggplot2. I expect that researchers and students will modify the scripts given here to create their own graphs. This obviously requires some working knowledge of the ggplot2 package, for which I will not give details here on specific functions, arguments and choices that I selected (as an introduction to ggplot2, I would especially recommend a two-part online workshop given by Thomas Lin Pedersen).